2011
DOI: 10.1186/1757-1146-4-27
|View full text |Cite
|
Sign up to set email alerts
|

Patient expectations of podiatric surgery in the United Kingdom

Abstract: BackgroundPatient expectations can be difficult to conceptualise and are liable to change with time, health and environmental factors. Patient expectation is known to influence satisfaction, however little is known about the expectations of patients attending for podiatric surgery. This paper will explore the expectations of a large cohort of patients undergoing elective foot surgery.MethodsThe UK based podiatric audit of surgery and clinical outcome measurement (PASCOM) audit system was applied to a consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 35 publications
(50 reference statements)
1
13
0
Order By: Relevance
“…Previous studies addressed only individual diagnoses 21,24 or developed nonquantifiable means of assessing expectations. 19,23 Younger et al 24 compared expectations and satisfaction between patients undergoing total ankle replacement (TAR) and ankle fusion. Patients undergoing TAR had significantly higher preoperative expectations than those undergoing fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies addressed only individual diagnoses 21,24 or developed nonquantifiable means of assessing expectations. 19,23 Younger et al 24 compared expectations and satisfaction between patients undergoing total ankle replacement (TAR) and ankle fusion. Patients undergoing TAR had significantly higher preoperative expectations than those undergoing fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Authors showed that while the degree of deformity correction did not improve QoL, achieving free choice of shoe wear had a positive effect on the QoL outcome. Conversely, Wilkinson et al, 27 studying patient expectations of foot surgery in the United Kingdom, reported that cosmesis was a relatively uncommon expectation and reported in only 12% of patients. Furthermore, when specifically addressing the issue of improved appearance in terms of achieving a narrower foot following hallux valgus surgery, Tai et al 24 reported that among females, this ranked only as the 10th criteria in order of importance in patients' expectations.…”
Section: Discussionmentioning
confidence: 99%
“…Patients attending for podiatric surgery typically expect pain relief, followed by improved mobility and shoe fitting [30,36]. …”
Section: Discussionmentioning
confidence: 99%